Kontribusi Delapan Standar Nasional Pendidikan terhadap Pencapaian Prestasi Belajar - Sabar Budi Raharjo (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2014)
National education standards is a means to ensure the quality of educational services. School administrators must fulfill minimum standards in helping students to achieve learning target. The purpose of this study was to determine the achievement of national education standards and the extent to which they contribute to eight national education standards towards the learning achievemen of high school students. The research method is a survey. The results showed that first, among the achievement of eight national education standards, educational facilities and infrastructures standards, process standards competency standards and education professional standards were considered low. Second, the eight national education standards contribute less significant to student national examination score. This means that successful learning achievement is determined by other factors, both internal and external, such as motivation, interest, parental background, school environment. From the eight standards, teacher and education personnel standard give significant influence to national students exam results. The first conclusions is that, four standards with below average accreditation credits are educational facilities and infrastructures standards, process standards, competency standards, and education professional standards. Secondly, the contribution of eight national standards of education is still relatively less and other factors are needed in order to improve the students’ learning achievement.ABSTRAK Standar nasional pendidikan merupakan sarana untuk menjamin mutu layananpendidikan. Dalam memberikan layanan pendidikan pengelola sekolah berusaha memberikan standar minimal kepada peserta didik dalam mencapai prestasi belajar. Tujuan penelitian ini yaitu untuk mengetahui ketercapaian standar nasional pendidikan dan sebesarapa besar kontribusi delapan standar nasional pendidikan terhadap pencapaian prestasi belajar siswa SMA. Metode penelitian adalah survei. Hasil penelitian menunjukkan bahwa: 1) dari delapan standar yang ada, standar yang masih rendah adalah standar sarana-prasarana, standar proses, standar kompetensi, dan standar tenaga pendidik dan kependidikan; 2) Delapan standar nasional pendidikan terhadap prestasi belajar (UN) tidak terlalu signifikan. Hal ini berarti bahwa keberhasilan prestasi belajar ditentukan oleh faktor lain baik internal maupun eksternal seperti motivasi, minat, latar belakang orang tua, dan lingkungan sekolah. Dari 8 standar tersebut, standar yang memiliki pengaruh signifikan terhadap UN adalah standar pendidik dan tenaga kependidikan (PTK). Simpulan dari penelitian ini: 1) empat standar yang masih rendah perolehan angka akreditasi yaitu standar sarana-prasarana, standar proses, standar kompetensi dan, standar tenaga pendidik dan kependidikan masih rendah; 2) kontribusi delapan standar masih relatif kecil dan perlu memperhatikan faktor lain di luar standar dalam perbaikan mutu prestasi belajar.